Indicative Relevant Publicity of Lithuanian Agricultural Sector in the Global Market - AMBRAZIŪNAITĖ, DIANA (Jaunųjų mokslininkų darbai, 2017)
The Revealed Comparative Advantage (RCA) index was used to assess and analyze the international competitiveness of the Lithuanian horticulture sector. The RCA index was chosen for the following reasons: sales of individual vegetable products have been increasing for several consecutive years, new and expanding existing foreign markets were created. While analyzing the RCA theories the following main elements of the purpose are distinguished: the study of international trade relations; country specialization identifying weak and strong branches / sectors; the indicator of international competitiveness and the index of the efficiency of international trade. The article analyzes the general category1 of vegetables, some roots and tubers and the categories of individual product groups2 of this cattery which are compiled according to the International Trade Center3 year of 2011 to 2016. The results of the research showed that Lithuania specializes in exporting vegetables and some roots and tubers to international markets, and many vegetable groups have a discovered relative advantage. RCA from 2011 to 2016 did not have three vegetable and several root vegetable groups and tubers: frozen and dried vegetables, manioc, marantos and other similar roots and tubers. A significant variation in the RCA indices of vegetables and some root and tuber products indicates a lack of stability in international trade and a strong upward or downward trend in competitiveness. 1HS4 07. 2HS6 0701-0714 – categories of product groups. 3Trade Map data baze, Page online: www.trademap.org.